PHYTOCHEMICAL ANALYSIS, IN VITRO EVALUATION OF ANTIOXIDANT AND FREE RADICAL SCAVENGING ACTIVITY OF LEAVES OF TRICHOPUS ZEYLANICUS SSP TRAVANCORICUS BURKILL EX K. NARAYANAN (TRICHOPODACEAE) - K.M.S. Maruthi Rajaguru; S. Sridhar (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Free radicals are an outcome of various metabolic activities and their excess production leads to many diseases. Therefore, it is necessary to neutralize excess free radicals. Free radical scavenging activity of various extracts of Trichopus zeylanicus ssp travancoricus leaf was evaluated using different assays. Petroleum ether, benzene, ethyl acetate, methanol and ethanol extracts of Trichopus zeylanicusssptravancoricus scavenged DPPH, hydroxyl, superoxide, ABTS free radicals and increased reducing potential in a concentration dependent manner. Maximum DPPH and superoxide radical scavenging activity of methanol extract was recorded whereas ethyl acetate extract showed enhanced hydroxyl radical scavenging activity. Ethanol extract showed the highest ABTS radical cation scavenging activity. The reducing power of the T. zeylanicusssptravancoricus was in following order: ethanol > methanol > petroleum ether > ethyl acetate > benzene. The qualitative phytochemical analysis revealed the presence of important phto constituents. These results are an indication of antioxidant potential of the extracts and may be responsible for some of the therapeutic uses of T. zeylanicus ssp travancoricus.